CELEBRATION OF THE MAWLID OF PROPHET MUHAMMAD SAW: RITUAL AND SHARE ISLAM VALUE IN INDONESIAN - Sardjana Orba Manullang; Risa Risa; M Trihudiyatmanto; Fina Amalia Masri; Aslan Aslan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Mawlid celebrations in several countries have become a sacred and festive agenda. The agenda was enlivened with great festivities and rituals to broadcast the struggle of the Prophet Muhammad to the people from the past until now. The purpose of this paper is to analyze the annual Mawlid celebration, between the ceremony and the nuances of rituals or symbols of Islam in Indonesia. This article is carried out by reviewing literature on ten international publications and other literature that has successfully discussed the celebration of the Prophet's Birthday or Maulid Nabi by Muslims, then analyzed in depth so that the results are valid and reliable with a phenomenological approach. The findings of this study are Muslims who hold Maulid celebrations equipped with rituals and announcements on a large scale. The celebration of Maulid provides an Islamic atmosphere for Muslims to learn about the history of the Prophet and to establish and participate in friendship with fellow believers who lived 14 different centuries from the Prophet in the struggle of Islam.